2012
DOI: 10.1590/s1808-86942012000300020
|View full text |Cite
|
Sign up to set email alerts
|

Otoproteção em cobaias expostas a agrotóxico e ginkgo biloba

Abstract: Pesticides are widely used in agriculture, despite the risk of hearing loss related to the exposure to their chemical components. This study looks into protective drugs to counteract the ototoxicity of pesticides. Objective This study aims to analyze the effect ginkgo biloba extract may have in protecting against possible cochlear damage caused by organophosphate pesticides (methamidophos). Anatomic changes are assessed through surface and electron microscopy. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…Based on all four studies, we can totally conclude that carbon tetra- The structure of the main part of cochlea including hair cells, named organ of corti, in guinea pigs was analyzed by means of the electron microscopy and the results indicated that GBLE (100 mg/kg/day, 90 min before methamidophos administration) prevented the organ of corti structural deformation (Finkler et al, 2012).…”
Section: Carbon Tetrachloride (Ccl 4 )mentioning
confidence: 95%
“…Based on all four studies, we can totally conclude that carbon tetra- The structure of the main part of cochlea including hair cells, named organ of corti, in guinea pigs was analyzed by means of the electron microscopy and the results indicated that GBLE (100 mg/kg/day, 90 min before methamidophos administration) prevented the organ of corti structural deformation (Finkler et al, 2012).…”
Section: Carbon Tetrachloride (Ccl 4 )mentioning
confidence: 95%
“…In the case of insecticide, Finkler et al 102 looked into the impact of GBE on the ototoxicity caused by organophosphorus insecticide (0.3 and 3 µg g −1 of methamidophos per day, 7 days). In guinea pigs, the core section of the cochlea was studied using an electron microscope.…”
Section: Gbe's Protective Effect Against Pesticidesmentioning
confidence: 99%
“…GBE's phytoconstituents acted on the oxidative phosphorylation of mitochondrial RNA and the Golgi apparatus at the intracellular level, aiding DNA repair mechanisms and boosting the "antioxidant status" by increasing intracellular glutathione levels and decreasing 3H-timi-dina21 incorporation. Finkler et al 102 found no damage to the outer ciliary cells on scanning electron microscopy, or to the basal turn of the cochlea, or the E2 and E3 turn, after 7 consecutive days of pesticide used at doses of 0.3 µg g −1 day −1 and 3 µg g −1 day −1 , when used in combination with GBE, in tandem with Fukaya and Kanno. 103 Also, diazinon is a pesticide used in agricultural applications.…”
Section: Gbe's Protective Effect Against Pesticidesmentioning
confidence: 99%
“…With a well-established safety profile and known antioxidant properties (Le Bars and Kastelan 2000;McKenna, Jones, and Hughes 2001), ginkgo biloba has been examined for prevention of hearing loss in animal model experiments and human trials (Fukaya and Kanno 1999;Huang, Whitworth, and Rybak 2007;Dias 2010;Cakil et al 2012;Finkler et al 2012;Dias et al 2015;Ma et al 2015). However, results from these studies have shown weak evidence of efficacy to date.…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…Kastelan (2000),McKenna, Jones, and Hughes (2001), Cakil et al (2012),Dias et al (2015),Dias (2010), Huang, Whitworth, and Rybak (2007), Finkler et al (2012,Fukaya and Kanno, (1999) andMa et al (2015) N-acetylcysteine (NAC)-Aminoglycosides -Cisplatin -NoiseNCT01271088Bock et al (1983),Kramer et al (2006),Kocyigit (2011), Tokgoz et al (2011), Kranzer et al (2015,Yoo et al (2014) and Riga et al…”
mentioning
confidence: 99%